Hadith #3709 - Sunan Abi Dawud - Abdullah bin al-Dayli; Abu 'Amr al-Saybani أبو عمرو السيباني; Dmrh bin Rabi'ya al-Flstyny ضمرة بن ربيعة الفلسطيني أبو عبد الله; Fyrwz al-Dylmy (Sunan Abi Dawud)
I am afraid it may not be muzza from which(the people of) ‘Abd al-Qais were prohibited. I asked Qatadah : What is muzza’? He replied: Drink of dates made in a green jar and vessels smeared with pitch.
Grade: Da'if